1987
DOI: 10.1038/bjc.1987.166
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy in the normal rat colon with phthalocyanine sensitisation

Abstract: Summary Photodynamic therapy (PDT) involves the interaction of light with an administered photosensitising agent to produce cellular destruction. It has promising potential for the local and endoscopic treatment of gastrointestinal cancer. There is however little data on the response of normal intestine to PDT.We have investigated the use of a new photosensitiser chloro aluminium sulphonated phthalocyanine (AlSPc) for colonic PDT. The peak concentration of AISPc in the colon measured by alkali extraction oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 13 publications
4
35
0
Order By: Relevance
“…5 The nature of damage in tumours seen in this study was similar with an initial vascular dilatation, haemorrhage, and subsequent shutdown. Figure 5 shows a tumour 48 hours after photodynamic therapy.…”
Section: Photodynamic Therapy Of Dimethylhydrazine Tumourssupporting
confidence: 68%
“…5 The nature of damage in tumours seen in this study was similar with an initial vascular dilatation, haemorrhage, and subsequent shutdown. Figure 5 shows a tumour 48 hours after photodynamic therapy.…”
Section: Photodynamic Therapy Of Dimethylhydrazine Tumourssupporting
confidence: 68%
“…We have previously reported the efficacy of aluminium sulphonated phthalocyanine (AlSPc) as a photosensitiser in both normal tissue and tumours (Barr et al, 1987a;Tralau et al, 1987;Barr et al, 1990) as well as its advantages over haematoporphyrin derivative with respect to cutaneous phototoxicity (Tralau et al, 1989). We have further observed that PDT using AlSPc does not compromise the mechanical strength of the normal colon (Barr et al, 1987b).…”
mentioning
confidence: 62%
“…These results show broad correlation with the corresponding mucosal fluorescence measurements from the CCD imaging studies with greatest damage also found at 4 h (mean diameter 9.1 ± 1.5 mm) with no visible necrosis at 24 h. The notable exception was at 30 min where considerable necrosis was seen (mean diameter 7.2 ± 1.0 mm) even though mucosal fluorescence was more than an order of magnitude lower than at 4 h. Histological examination was undertaken on all specimens showing macroscopic necrosis 72 h after laser treatment. At all treatment times after introduction of ALA, an acute inflammatory infiltrate, mainly comprising of monocytes and polymorphonuclear neutrocytes, was seen throughout all tis- Barr et al, 1987). It is reassuring that necrosis does not extend into the muscle layer, although there is evidence of an inflammatory infiltrate.…”
Section: Phototherapy Studiesmentioning
confidence: 72%